SOSIALISASI DAN PENYULUHAN KOPERASI SIMPAN PINJAM - Arif Fajar Wibisono (Asian Journal of Innovation and Entrepreneurship, 2014)
Dusun Deles, Jogonayan Village, District Ngablak, Magelang, Central Java Province thatconsisting of 3 RW and 12 RT. Mostly livelihood society are farmers.They sold their agriculturalproducts themselves to the market or to the middlemen or taken buy the buyer. So far thesociety determines the gain or loss only to the extent of the advantages or disadvantages oftheir capital.Besides as a farmer, the societyalso worksas traders, civil servants, workers, etc.The society in Dusun Deles are a society that have high desire to advance Dusun Deles, Thiscan be proved on the willingness of the society to work together for the develpoment of DusunDeles. The level education of Dusun Deles Society is below the average. Mostly, the education ofthe society were only maximum of Junior High School.Due to the low level education, the society awareness become less when it comes to education.The lack of public experience and lack of knowledge about the economy, led to the welfare ofsociety uneven. The low quality of human resources led theauthor to discuss about maximizingthe potential yield of the farmers more optimal. The author tried to increase the role of creditunions to help the economy of Dusun Deles Society and also giving counseling, socialization,briefed on the priciple of profit and loss and also the principle  of prices and househol financialmanagement.